Disfungsi Keluarga Pada Masyarakat Kelurahan Kampung Baru - Sely Monica; Sri Wahyuni; Rahma Syafitri (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
This study describes how dysfunction in the family up to divorce leads to the religious court in Kampung Baru sub-district, Tanjung Pinang Barat. The purpose of the researcher is to discuss how family functions do not work in the new village. This study analyzed theoretically sociology to know about family functions that are applied and not implemented in the family. Approach This study uses a qualitative research method with a descriptive approach by means of data collection techniques in this study using semi-structured interviews, observation and documentation, determining informants using Purvose sampling technique with 6 informants, namely 2 informants as perpetrators of family functions not working, 2 informants as victims of family dysfunction, and 1 religious court staff informant in tanjungpinang. The results of this study indicate several family functions that do not work in some communities in the new village such as the function of love which does not work resulting in infidelity, the reproductive function which does not work resulting in divorce within the family and the economic function which does not work resulting in abandonment of families such as children whose needs not enough.